Using Educational Technology to Reduce Learning Loss During the COVID-19 Pandemic - Bambang Gulyanto; Dewi Purnama Sari (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study is to describe how educational technology was used to minimize learning loss at Senior High School. The COVID-19 pandemic has had a negative impact on education in schools. The ability of students to achieve competence and learning objectives is weaker than before. This phenomenon is termed "learning loss." Therefore, to support the objectives of this study, a descriptive qualitative research method was used. The data was obtained through questionnaires. The data analysis technique uses a data triangulation technique. The research results show that using technology to minimize learning seems successful. This can be seen from the results of a questionnaire on 125 students, namely: 1) 73% of students have a positive perception of learning technology; 2) 45% of students agree that it is not boring; 3) 80% of students increased their motivation to study during the COVID-19 pandemic; 4) 87% of students say learning technology is very useful; 5) And 66% of students think that learning technology was effective during the Covid-19 pandemic. Apart from that, of the five indicators studied, all indicators have a positive correlation with the use of learning technology during the Covid-19 pandemic.